Size Impact of Ordered P3HT Nanofibers on Optical Anisotropy. Issue 9 (18th February 2016) - Lobov, Gleb S.; Zhao, Yichen; Marinins, Aleksandrs; Yan, Min; Li, Jiantong; Sugunan, Abhilash; Thylén, Lars; Wosinski, Lech; Östling, Mikael; Toprak, Muhammet S.; Popov, Sergei
Abstract : Poly‐3‐hexylthiophene (P3HT) nanofibers are 1D crystalline structures with semiconductor properties. When P3HT nanofibers are dispersed in nonconducting solvent, they react to external alternate electric field by aligning along the field lines. This can be used to create layers of ordered nanofibers and is referred to as alternating current poling method. P3HT nanofibers with three different size distributions are fabricated, using self‐assembly mechanism in marginal solvents, and used for the alignment studies. Anisotropic absorption of oriented 2 μm long nanofibers exponentially increases with the magnitude of applied field to a certain asymptotic limit at 0.8 V μm −1, while 100–500 nm long nanofibers respond to electric field negligibly. Effective optical birefringence of oriented 2 μm long nanofibers is calculated, based on the phase shift at 633 nm and the average layer thickness, to be 0.41. These results combined with further studies on real‐time control over orientation of P3HT nanofibers in liquid solution or host system are promising in terms of exploiting them in electroabsorptive and electrorefractive applications. Abstract : Poly‐3‐hexylthiophene (P3HT) nanofibers can react to external electric field by aligning along the field lines. The anisotropy of aligned nanofibers depends on their lateral size and the poling voltage. The effective birefringence for long nanofibers is 0.41, which is larger than for typical uniaxial crystals. Mentioned results, together with the technique of real‐time orientation control, can be utilized in electro‐optical applications.